Distribution of transaction costs in the investment and construction sector of the Russian Federation - R. R. Kozakov; V. A. Koshcheev (Vestnik MGSU, 2023)
Introduction. The relevance of the analysis of transaction costs is associated with a significant share of the transaction sector in the gross domestic product (GDP) of the national economy, a change in which can be associated with both the efficiency and inefficiency of the built institutional environment. The purpose of the study is to develop recommendations for influencing the elements of the institutional environment to optimize administrative barriers typical for the investment and construction sector (ICS) of the Russian Federation. The novelty of the author’s approach is formed by considering the aspect of distribution of transaction costs under the influence of heterogeneous contracts between the participants of the ICS.Materials and methods. The data of Rosstat on the structure of the gross domestic product of the Russian Federation are used, the results of international studies on quantitative and qualitative assessment of transaction costs in construction are analyzed. The study was based on the tools of institutional theories, as well as general scientific methods.Results. Distributors of transaction costs in the investment and construction sector of the Russian Federation are revealed: customer predictability, institutional rent of the contractor, institutional rent of the developer, completeness of relational contracts to ensure customer predictability, information on the profitability of bypassing formal rules by subjects of the investment and construction sector, digitalization.Conclusions. The description of transaction costs through the aspect of their distribution allows to formalize a model of their quantitative or qualitative measurement, taking into account the impact of the institutional environment in the Russian Federation.